PALEOZOIC STAGE OF THE DON-MEDVEDITSA DISLOCATIONS DEVELOPMENT (EAST EUROPEAN PLATFORM) - Bolotov S.N.; Ustinova M.A.; Nikolaev V.G. (My University, 1999)
Using the Berezovo area of the Don-Medveditsa dislocations, the Paleozoic history of the region is reconstructed using a new method of computer data processing, which allows one to plot paleostructural maps. It was found that some of the Don-Medveditsa dislocations had been formed as far back as the Early Devonian. During the Devonian-Early Carboniferous, these folds experienced at least three phases of tectonic reactivation.
Keywords: DISLOCATIONS DEVELOPMENT; COMPUTER DATA PROCESSING; TECTONIC REACTIVATION